Photo-Fenton Treatment of Antibiotic Wastewater - Elmolla, E. S.; Chaudhuri, M. (Technoscience Publications, 2010)
The study examined photo-Fenton treatment of an antibiotic wastewater containing amoxicillin and cloxacillin, and evaluated the effect of operating conditions (H2O2/COD molar ratio and H2O2/Fe2+molar ratio) on biodegradability(BOD5/COD ratio) improvement and mineralization. The optimum operating conditions for treatment of the antibiotic wastewater was observed to be H2O2/COD molar ratio 2.5 and H2O2/Fe2+ molar ratio 20 (COD/H2O2/Fe2+ molar ratio 1/2.5/0.125) at pH 3 and reaction time 30 min. Under optimum operating conditions, complete degradation of amoxicillin and cloxacillin occurred in one minute, biodegradability improved from 0.09 to 0.50 ± 0.01 in 30 min, and COD and DOC removal were 67 ± 1% and 51 ± 2%, respectively in 30 min. The study indicated that the photo-Fenton process can be used as pretreatment for antibiotic degradation and biodegradability improvement of antibiotic wastewater containing amoxicillin and cloxacillin.